Factors associated with smoking cessation in early and late pregnancy in the smoking, nicotine, and pregnancy trial: a trial of nicotine replacement therapy - Vaz, Luis R.; Leonardi-Bee, Jo; Aveyard, Paul; Cooper, Sue; Grainge, Matthew; Coleman, Tim (Oxford University Press, 2014)
Introduction: Previous studies have found partners’ smoking status, multiparity, and nicotine dependence to be associated with smoking cessation in pregnancy. However, no studies have investigated influences on cessation among women using nicotine replacement therapy (NRT). We analyzed data from a trial of NRT in pregnancy to determine factors associated with shorter- and longer-term cessation.